Особенности оценивания неопределенности измерения эталона напряженности импульсных электрических и магнитных полей - Шевченко, Н. С. (Weber, 2010)
The procedure of estimation of uncertainty of measurements on the standard of units of the maximum values of intensity of electric and magnetic pulse fields is considered
Keywords: измерение эталона напряженности